2005
DOI: 10.1088/0953-4075/38/9/027
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry with synchrotron radiation

Abstract: Synchrotron radiation is a good mimic of solar radiation and therefore has been widely used to study photo-induced physics and chemistry in the terrestrial atmosphere. In this paper we review how synchrotron radiation is being used as a tool for investigating atmospheric physics and chemistry with particular emphasis on studies related to ozone depletion, global warming and ionospheric phenomena. The paper concludes with a discussion of the new possibilities that the next generation of synchrotron-based light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…1 The present work is part of a wider research programme aimed at understanding the spectroscopy of sulphur-containing species and the role of these gases in atmospheric chemistry and physics (see, e.g., Refs. [2][3][4]. In order to model these processes in the stratosphere and troposphere, absolute photoabsorption cross sections (oscillator strengths) of such compounds are needed as well as a detailed knowledge of their electronic state spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1 The present work is part of a wider research programme aimed at understanding the spectroscopy of sulphur-containing species and the role of these gases in atmospheric chemistry and physics (see, e.g., Refs. [2][3][4]. In order to model these processes in the stratosphere and troposphere, absolute photoabsorption cross sections (oscillator strengths) of such compounds are needed as well as a detailed knowledge of their electronic state spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Trifluoromethyl sulphur pentafluoride, SF 5 CF 3 , has recently been termed the super greenhouse gas. This claim to fame arises because, per molecule, it makes more contribution to global warming via the greenhouse effect than any other molecule yet detected in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This claim has since been disputed [3]. Infrared (IR) absorption measurements showed that SF 5 CF 3 has the highest radiative forcing per molecule of any gas found in the atmosphere to date (0.57 W m -2 ppb -1 , a figure since updated to 0.60 ± 0.03 W m -2 ppb -1 [4,5]). Antarctic firn measurements suggested that it has grown from a concentration of near zero in the late 1960s to ca.…”
Section: Introductionmentioning
confidence: 99%
“…The recent identification of the need for more data on electronic state spectroscopy and subsequent photodissociation and photoionisation pathways leading to chemical reactivity has highlighted the need for more fundamental studies of PA and PE in a wide range of molecules for which such data has not been generated these include biomolecular targets (for radiation chemistry and radiotherapy) [12]; Volatile Organic Species (VOCs) for environmental studies of atmospheric/biosphere interface [13] and a range of compounds used in next generation industries (e.g. replacements for fluorocarbons used in plasma etching) [14,15].…”
Section: Introductionmentioning
confidence: 99%